Exploring Students’ Writing Performance through Corrective Feedback - Masrul; Wicaksono, Bayu Hendro (Penerbit STKIP PGRI Bangkalan, 2024)
Prior studies on corrective feedback have highlighted the effect of feedback on students writing accuracy. In this present study, the impacts of corrective feedback on students’ writing performance; grammatical accuracy, complexity, fluency, content and organization, appropriateness, argumentation, interpersonal, textual, lexical were examined. Participants were 96 students who were assigned into different groups to accept written corrective feedback, content and organization of ideas, multilateral feedback (i.e., on grammatical accuracy, complexity, fluency, appropriateness, argumentation, interpersonal, textual, lexical), and control group that did not accept any feedback during learning sessions. Pre-test, post-test and delayed post-test and weekly writing revisions were carried out. The results showed that the four experiment groups showed significant improvements. The results of this study showed that students had language learning potential which can be enhanced when teachers provide corrective feedbacks. This study suggested that students’ writing skills can be improved by providing sustained feedback.